2020
DOI: 10.1177/2633489520959072
|View full text |Cite
|
Sign up to set email alerts
|

The role of clinical champions in facilitating the use of evidence-based practice in drug and alcohol and mental health settings: A systematic review

Abstract: Background: The dissemination and adoption of research into clinical practice in health care settings is a complex and challenging process. Clinical champions have been increasingly used in health care to facilitate the implementation and adoption of evidence-based practice and to overcome organizational barriers. In relation to substance use and mental health disorders, translation of new evidence into practice is an ongoing challenge. The utilization of a clinical champion to motivate staff to implement evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 57 publications
1
75
0
1
Order By: Relevance
“…Development of the proposed model was guided by existing literature on champions. Given the recent integrative review on champions in health care ( Miech et al, 2018 ) and systematic review on clinical champions in substance use and mental health ( Wood et al, 2020 ), a new systematic review did not seem warranted. Instead, the model development drew upon the work of these two reviews, relevant studies published after these reviews, and foundational work on champions published in non-health-related sources.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Development of the proposed model was guided by existing literature on champions. Given the recent integrative review on champions in health care ( Miech et al, 2018 ) and systematic review on clinical champions in substance use and mental health ( Wood et al, 2020 ), a new systematic review did not seem warranted. Instead, the model development drew upon the work of these two reviews, relevant studies published after these reviews, and foundational work on champions published in non-health-related sources.…”
Section: Methodsmentioning
confidence: 99%
“…First, champions historically were thought of as being emergent—individuals who assumed the role of champion for a cause they believed in ( Howell and Higgins, 1990b ; Schon, 1963 ). However, in current practice, many organizations appoint individuals to champion roles as an implementation strategy ( Wood et al, 2020 ). This distinction between emergent and appointed champions has been recognized in the literature ( Damschroder et al, 2009 ; Soo et al, 2009 ); however, we do not have much evidence about differential effects of emergent and appointed champions, let alone why one type may be more effective than the other.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to do this is by identifying a champion within the school, defined as someone whose role is to help others see the advantages of making a change, mentor them through the change, and ultimately persuade others to adopt a new practice (Cranley et al, 2017 ). Indeed, a recent meta-analysis found that champions are critical to influencing organizational structures, as evidenced by increased staff engagement, motivation, and faster adoption and persistence in the delivery of interventions (Wood et al, 2020 ). Research also suggests a two-step process often exists for champion-driven dissemination and adoption.…”
Section: Determinantsmentioning
confidence: 99%
“…Lastly, while there is limited existing research into the process domain 59 , clinical champions have generally been perceived as a facilitator of implementation efforts 60-63 . There is also evidence to suggest that clinical champions contribute to a faster uptake and sustained use of the intervention 64 , and that they can assist with generating enthusiasm amongst staff, despite systemic barriers 65-67 .…”
Section: Discussionmentioning
confidence: 99%